What Is It Like to Be an Alien?. Issue 4 (28th March 2016) - Matravers, Matt
Abstract: This brief article is concerned with an aspect of Jonathan Glover's book, Alien Landscapes ?. After reflecting a little on the book as a whole, the question that is taken up is, 'Why might a book that seeks to help those without mental disorders understand what they are like "from the inside" be of interest to laymen and practitioners in the criminal law?'. One answer lies in part in the way that 'what it is like from the inside' might interact with judgements of criminal responsibility. Taking its cue from examples used by Glover the article considers, and puts pressure on, the 'dual view' he proposes: that when dealing with those with mental disorders we should treat them as responsible agents in the sense of not withholding from them Strawson's 'reactive attitudes', while nevertheless accepting that their personalities and behaviours are the results of large doses of 'bad luck'.